Ceramic Sales System At CV Cahaya Mulia Using Visual Basic 6.0 Applications - Setia Purwani Dewi; Cut Asiana Gemawaty, SKom., MMSI (Jurnal Sistem Informasi, 2006)
CV Cahaya Mulia is a form of trading business that specializes in the sale of goods - items of ceramics, bath, paint, faucets, toilet, sink. Necessary to improve marketing and processing of data handling good in trade that are developing However, the sales system has been run by CV Cahaya Mulia still using manual systems. Therefore, the author will give the proposal the existing manual system to a computerized system that can get results more effectively and efficiently.